Application of Perkin’s Reaction to Terpene Aldehyde β-cyclocitral. - Limaye, P.A.; Huddar, P.H.; Ghate, S.M. (Asian Journal of Chemistry, 2010)
Perkin's reaction has been successfully applied to β-cyclocitral. It appears Perkin's reaction could be applied to the above terpene aldehyde because of high electron density round π bonds in conjugation with aldehyde group making it more electronegative.